Revitalisasi Seni dan Budaya Betawi melalui Inovasi Berbasis Komunitas: Penelitian - Febi Ramadhani Rusdin; Felisianus Novandri Rahmat; Febrianto Saptodewo; Anita Anita; Adji Firmansyach; Giovino Dendah Alfahjar; Cherlie Augustina Sonia; Putri Auliya Saumi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This program aims to revitalize Betawi arts and culture through an innovative approach rooted in the strengths of local communities. In general, the program focuses on efforts to strengthen community and institutional capacity in preserving Betawi arts; develop an innovative marketing model for Betawi culinary products through the integration of design and media; and create a collaborative space that encourages greater public appreciation and participation in Betawi arts and culture. The implementation of the Betawi Arts and Culture Revitalization Program Through Community-Based Innovation is carried out through several stages, including socialization, training sessions, the application of technology and innovation, mentoring, evaluation, and sustainability planning. A series of trainings covering branding enhancement, financial management, and the use of social media provides practical knowledge and skills for community art studios and participating residents to build identity, increase independence, and promote artistic activities more strategically and sustainably. Thus, Betawi arts and culture are not only preserved, but are also able to take part in the dynamic life of a modern, inclusive, and adaptive urban society.